PENINGKATAN KEMAMPUAN MANAJEMEN PEMASARAN PRODUK UNGGULAN BERBAHAN DASAR NANEAS KECAMATAN MEKARSARI BARITO KUALA PROVINSI KALIMANTAN SELATAN - Syafril Syafril; Yuliani Yuliani; Muhammad Fahmi; Netti Rosiana Fadhilah; Jamaluddin Jamaluddin (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2020)
Community Service Activities by providing Training in Improvement of Marketing Management Capabilities of Leading Products Based on Pineapple in Mekarsari District are expected to increase the knowledge of SMEs, managers of BUMDES and village apparatus in marketing the products produced. One marketing technique that can be used is the marketing mix which is a combination of a number of marketing tools used by the company to convince the object of marketing or the intended target market. SMEs and BUMDES can increase sales by paying attention to products, prices, places and promotions. The combination of 4P in a product marketed will be able to increase the sales volume of SMEs in Mekarsari Barito Kuala District.